Socio-demographic, exercise, and anthropometric profiles of adults participating in fitness exercise programs in Vhembe district, Limpopo province, South Africa - Ramashidzha , Rendani Raymond; Makuse, Sefora Hazel; Masoga, Sylven (Indonesian Nutrition Association, 2025)
Introduction Adults in Vhembe district participate in fitness exercise programs for optimal health. However, the nutritional profiles of these participants remain unknown. Aim: To assess the socio-demography, calculate BMI and measure WC of adults participating in fitness exercise programs around Vhembe district, Limpopo Province. Method: A cross–sectional study design was conducted to assess socio-demographic and anthropometric profiles of 112 adults participating in fitness exercise programs around Vhembe district, Limpopo Province. Ethical clearance was obtained from TREC and written consent by the participants. Socio-demographic profile included, for example, age, education status, duration and frequency of training. Anthropometry included weight and height to calculate BMI, and waist circumference. Data were analyzed using SPSS (v29). The Chi-square test, with a p-value of <0.05, was used to determine the association among variables. Results: Males were aged 36.3±9.3 and females 32.1±8.7 years; training three times per week for two hours in aerobics and bodybuilding programs. Most participants had bachelor’s degrees (males, 35.5%; females, 29.8%) and diplomas (males, 32.3%; females, 27.7%). Unemployment was higher (57.4%) among females compared to males (38.5%). Aerobic participants were overweight (males, 27.8±4.7; females 28.8±4.8 kg/m²) whereas those in bodybuilding were obese (31.0±16.9, males and 37.5±0.0 kg/m², females). Participants in both programs had optimal waist circumferences (<102 cm, males and <88 cm, females). Anthropometry was associated (p<0.05) to demography among the aerobic exercise participants. Conclusion: Participants trained once per day, three times a week for two hours. The majority had higher education qualifications, however, unemployed. Participants were overweight with acceptable waist circumference values